Phenotypic and genotypic characterization of Staphylococcus aureus isolated from pork sausage (Research, Society and Development, 2021)
The objective of this study was to characterize the genotype and phenotype of S. aureus isolates from pork sausages. Fifty samples of pork sausages were collected, counts of coagulase-positive Staphylococcus were made and isolates were obtained to identify S. aureus species. In the isolates, the presence of genes sea, seb, sec, and sed was surveyed, the methicillin-resistance was assessed and the production of biofilm in Congo red agar, stainless steel, polyethylene, glass, and pork casing was tested. The capacity of biofilm formation was assessed after the exposure to sublethal stress. Of the samples tested, 12% had counts superior to what is permitted by the legislation. S. aureus was isolated in 44% of the samples. Of these, 54% had only the gene sed and 32% had genes sec and sed, 73% were classified as methicillin-resistant S. aureus (MRSA). Of the MRSA isolates, 62% had only gene sed and 35% had both genes found in this study. Regarding the biofilm formation in Congo red agar, 68% of S. aureus isolates were considered as biofilm formers. After undergoing the sublethal stress, most of the biofilm former isolates proceeded to form biofilm and the non-biofilm former isolates responded in a distinct manner. The condition in which the sublethal stress greatly induced the biofilm formation was the cold. Biofilm production was observed only in the stainless steel and pork casing in 71% and 57% of the isolates tested, respectively. Thus, we stress the importance of implementing good manufacturing practices within the industry to control microbial contamination and biofilm formation.